Microflora around teeth and dental implants - Mohammad Shahabouee; Mansour Rismanchian; Jaber Yaghini; Akram Babashahi; Hamid Badrian; Hossein Goroohi (Wolters Kluwer Medknow Publications, 2012)
Background: When an implant is exposed to oral cavity, its surface gets colonized by micro-organisms. The aim of this study is to comparatively assess the microbiological parameters in sulci around the teeth and the crowns supported by dental implants. Materials and Methods: In this prospective, cross-sectional study, 34 partially edentulous patients aged between 40 and 50 years with total 50 anterior maxillary single implants with cemented crowns (depth of sulci <4 mm) and 34 similar teeth in the same jaw of the same patients were included. Excluded were the patients with compromised systemic and periodontal health and smoking habits. None of the patients had used any antimicrobial mouthwashes during at least two weeks before the study. All of the implants (ITI) were at least 6 months in place covered by definitive prostheses. Samples of gingival sulci were taken around teeth with paper cone and transported to Stuart transport medium. Samples were cultured and examined by a dark field microscope and eight laboratory tests were performed to determine the micro-organisms The data were evaluated statistically using Chi-square test (a=0.05). Results: Six anerobic bacteria found in teeth and implants sulci were Gram-positive cocci, Gram-negative cocci, Prevotella, Porphyromonas gingivalis, Bacteroid Fragilis and Fusobacterium. Gram-positive cocci and Gram-negative cocci had maximum and minimum percentage frequency in the two groups, respectively. There were no significant differences between the two groups (P value >0.05). Conclusion: The present study indicated that microflora in implant sulci is similar to the tooth sulci, when the depth of sulci is normal (<4 mm). As a result, implants' susceptibility to inflammation is the same as teeth.